2017
DOI: 10.1080/03602532.2017.1322609
|View full text |Cite
|
Sign up to set email alerts
|

Ocular non-P450 oxidative, reductive, hydrolytic, and conjugative drug metabolizing enzymes

Abstract: Metabolism in the eye for any species, laboratory animals or human, is gaining rapid interest as pharmaceutical scientists aim to treat a wide range of so-called incurable ocular diseases. Over a period of decades, reports of metabolic activity toward various drugs and biochemical markers have emerged in select ocular tissues of animals and humans. Ocular cytochrome P450 (P450) enzymes and transporters have been recently reviewed. However, there is a dearth of collated information on non-P450 drug metabolizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…First pass metabolism is a process in which oral drug administration results in drug metabolism in the liver. When the drug passes directly from the intestine into the hepatic PV it is rapidly cleared in the liver via drug metabolizing enzymes, transporters and secretion through the bile (Andrews et al, 2017;Argikar et al, 2017;Mariappan et al, 2017;Miron et al, 2017). This rapid clearance of drugs decreases therapeutic efficacy of the orally administered drug.…”
Section: Bypass Of First Pass Metabolism In the Liver By Targeting Lymentioning
confidence: 99%
“…First pass metabolism is a process in which oral drug administration results in drug metabolism in the liver. When the drug passes directly from the intestine into the hepatic PV it is rapidly cleared in the liver via drug metabolizing enzymes, transporters and secretion through the bile (Andrews et al, 2017;Argikar et al, 2017;Mariappan et al, 2017;Miron et al, 2017). This rapid clearance of drugs decreases therapeutic efficacy of the orally administered drug.…”
Section: Bypass Of First Pass Metabolism In the Liver By Targeting Lymentioning
confidence: 99%
“…Although a complete ocular model for studying drug metabolism is not available, renewed emphasis on the eye could provide future model improvements. A question not answered by many models is the importance of the lens in xenobiotic metabolism in addition to its protective role, where glutathione S-transferase and N-acetyltransferase activities are important (Argikar et al, 2017a). Transitioning from healthy donors and nonpigmented animal models may or may not be an ideal model for studying ophthalmic disease state in humans.…”
Section: Models Of Ocular Drug Disposition and Toxicitymentioning
confidence: 99%
“…Finally, there is no knowledge on the ocular expression and activity of AADAC in the literature. 43 To understand the biotransformation capacity in the eye and the risk of the formation of toxic metabolites from extended drug exposure from ocular implants, the metabolic profiling of individual ocular tissues in all preclinical species and in humans is crucial. A more detailed characterization of the catalytic and expression properties of ocular esterases is also important in the design of ophthalmic (pro)drugs and drug conjugates and in understanding the hydrolysis of drugs entering the eye from the systemic circulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A review on global proteomics studies indicated that CES1 is detectable in most human ocular tissues except aqueous humor but quantitative expression data is nonexistent, and information on CES expression in other species is lacking, hampering translational studies. Finally, there is no knowledge on the ocular expression and activity of AADAC in the literature . To understand the biotransformation capacity in the eye and the risk of the formation of toxic metabolites from extended drug exposure from ocular implants, the metabolic profiling of individual ocular tissues in all preclinical species and in humans is crucial.…”
Section: Introductionmentioning
confidence: 99%